Dual Phases of Respiration Chain Defect-Augmented mROS-Mediated mCa2+ Stress during Oxidative Insult in Normal and ρ0 RBA1 Astrocytes. (4th March 2013) - Peng, Tsung-I; Lin, Muh-Shi; Jou, Mei-Jie
Abstract : Mitochondrial respiratory chain (RC) deficits, resulting in augmented mitochondrial ROS (mROS) generation, underlie pathogenesis of astrocytes. However, mtDNA-depleted cells ( ρ 0 ) lacking RC have been reported to be either sensitive or resistant to apoptosis. In this study, we sought to determine the effects of RC-enhanced mitochondrial stress following oxidative insult. Using noninvasive fluorescence probe-coupled laser scanning imaging microscopy, the ability to resist oxidative stress and levels of mROS formation and mitochondrial calcium (mCa 2+ ) were compared between two different astrocyte cell lines, control and ρ 0 astrocytes, over time upon oxidative stress. Our results showed that the cytoplasmic membrane becomes permeated with YO-PRO-1 dye at 150 and 130 minutes in RBA-1 and ρ 0 astrocytes, respectively. In contrast to RBA-1, 30 minutes after 20 mM H2 O2 exposure, ρ 0 astrocytes formed marked plasma membrane blebs, lost the ability to retain Mito-R, and showed condensation of nuclei. Importantly, H2 O2 -induced ROS and accompanied mCa 2+ elevation in control showed higher levels than ρ 0 at early time point but vice versa at late time point. Our findings underscore dual phase of RC-defective cells harboring less mitochondrial stress due to low RC activity during short-term oxidative stress but augmented mROS-mediated mCa 2+ stress during severe oxidative insult.